HOPEAPHENOL-O-GLYCOSIDE, A COMPOUND ISOLATED FROM STEM BARK Anisoptera marginata (Dipterocarpaceae) - Sri Atun (Indonesian Journal of Chemistry, 2009)
Isolation and structure elucidation of some compounds from stem bark of Anisoptera marginata had been done. The isolation of those compounds was carried out by chromatographyc method and structure elucidation was performed by interpretation of spectroscopic data, including UV, IR,  1H and 13C NMR 1D and 2D, and FABMS. From acetone extract stem bark A. marginata we isolated five known compounds namely bergenin (1), (-)-ε-vinipherin (2), (-)-ampelopsin A (3), vaticanol B (4), (-)-hopeaphenol (5), and a glycoside compound namely hopeaphenol-O- glycoside (6).